Prospective randomized comparison of vincristine, doxorubicin and dexamethasone (VAD) administered as intravenous bolus injection and VAD with liposomal doxurubicin as first-line treatment in multiple myeloma - Dimopoulos, M.A.; Pouli, A.; Zervas, K.; Grigoraki, V.; Symeonidis, A.; Repoussis, P.; Mitsouli, C.; Papanastasiou, C.; Margaritis, D.; Tokmaktsis, A.; Katodritou, I.; Kokkini, G.; et al. (Annals of Oncology, 2003)
Background: The combination of vincristine and doxorubicin administered as a continuous infusion via an indwelling catheter together with intermittent high-dose dexamethasone (VAD) is an effective primary treatment for patients with symptomatic multiple myeloma. In order to avoid the need for an indwelling catheter, which imposes logistic problems for outpatient administration, several phase II studies have explored the feasibility and efficacy of VAD-like outpatient regimens. We designed a prospective randomized study to compare the objective response rates of two VAD-like outpatient regimens as primary treatment for symptomatic patients with multiple myeloma. Patients and methods: Patients were entered in a randomized study regardless of age, performance status and renal function. One hundred and twenty-seven patients received VAD bolus, which consisted of vincristine 0.4 mg i.v., doxorubicin 9 mg/m2 i.v. and dexamethasone 40 mg p.o. daily for four consecutive days and 132 patients received VAD doxil, which consisted of vincristine 2 mg i.v. and liposomal doxorubicin 40 mg/m2 i.V. on day 1 and dexamethasone 40 mg p.o. daily for 4 days. The two regimens were administered every 28 days for four courses and in courses 1 and 3, in both arms, dexamethasone was also given on days 9-12 and 17-20. Results: An objective response was documented in 61.4% and 61.3% of patients treated with VAD bolus and VAD doxil, respectively. Hematological and non-hematological toxicities were mild or moderate and equally distributed between the two treatment arms with the exception of alopecia, which was more common after VAD bolus, and of palmar-plantar erythrodysesthesia, which was more common after VAD doxil. Conclusions: Our multicenter trial, which included an unselected patient population, indicated that both VAD bolus and VAD doxil can be administered to outpatients and can provide an equal opportunity of rapid response in many patients with multiple myeloma.
Keywords: Chemotherapy; Liposomal doxurubicin; multiple myeloma